Entrepreneurship With Additive Manufacturing: Implications of Complexity Freedom in Product and Firm Ideation - Esparza Flores, Jose Antonio (Auckland University of Technology, 2020)
The diffusion of 3D printing technologies after the expiration of key patents in 2009 brought novel manufacturing applications beyond prototyping (Thompson et al., 2016). Particularly, Additive Manufacturing (AM) has enabled more integrated strategies for new product development and fabrication. As a result, AM has been considered as a promising instrument for new business creation (Rayna & Striukova, 2016). Studies concerning AM and entrepreneurial activity rarely consider the interactions with technology. Yet, theories that describe the relationship between product architecture and manufacturing organizations suggest that greater flexibility in product architecture would bring greater flexibility to the creation of the firm through a process of mirroring (Colfer & Baldwin, 2016). Additionally, the theory of effectual entrepreneurship describes the creation of markets as negotiations between entrepreneurs and possible partners with the product and the means of the entrepreneur at the centre of such negotiations (Sarasvathy & Dew, 2005; Zahra et al., 2006). The research presented in this thesis examines the idea that flexible product architecture in 3D printing gives entrepreneurs greater flexibility in product design and an increased flexibility in the acquisition of partners. Two studies were carried out under a grounded methodology to explore the effects of complexity in the ideation of business opportunities. Both studies are based on design exercises that study the impact of idea generation using imaginary images, sketches, and prototypes in design (Finke, 1996; Kudrowitz & Wallace, 2013). The first study included seven teams of participants who used a building set with the same budget conditions and objectives. The control group received traditional production costing, while the AM one received free complexity costing. Idea complexity was measured in the number of blocks used to build each component, and the number of connections in each joint. The second study consists of an ideation exercise where 308 participants interpreted abstract randomized images of objects of varying complexity to imagine possible future product and firm participants. Their responses were analysed to extract networks of product categories and stakeholder identities. Answers were evaluated in terms of novelty, literality, and network composition. The results of both studies challenge some of the arguments that explain the benefits of additive manufacturing as increased freedom in product design. Instead, the results suggest that complexity freedom is filtered through the manipulation of morphology in design exploration. This argument advocates for an embodied design exploration where the perceptual features of technology influence ideation. This thesis contributes to the understanding of the relationships between additive manufacturing, entrepreneurship, and design. The studies presented here highlight the need to reconsider claims made in recent years about the advantages of increased flexibility for entrepreneurship with the introduction of additive manufacturing. In addition, the focus on technological interfaces expands the domain of entrepreneurship and firm design including perception, which is not accounted for in strategy and business modelling.
Keywords: Entrepreneurship; 3D printing; Additive manufacturing; Creativity; Firm design